PENGEMBANGAN LKS SERTA PENERAPANNYA DALAM PEMBELAJARAN KOOPERATIF TIPE STAD MATA PELAJARAN FISIKA SEKOLAH MENENGAH ATAS NEGERI 1 WAY JEPARA T.P. 2019/2020: Sutimin - Sutimin (JPPG : Jurnal Pengembangan Profesi Guru, 2022)
Abstract This study aims to improve the appropriate learning implementation plan; The final assessment refers to the learning objectives; Increasing the value of learning outcomes. The research took place in three cycles, STAD learning with the help of LKS in the first cycle of groups based on the results of the free test, high grade students being trained by the teacher to help their peers controlled by the teacher, STAD learning with the help of LKS in the second cycle of groups based on the results of the first cycle test, high grade students To help peers, STAD learning with the help of LKS in the third cycle of groups is based on the results of the second cycle of tests. Data were collected by observation, questionnaires, tests and analyzed descriptively quantitatively. The results of this classroom action research: The teacher is able to design the right lesson plans with the help of LKS; Implementation of proper learning because student learning activities have increased from the first cycle to the third cycle; There is an increase in the value of learning outcomes from cycle 1 to cycle 3, because the evaluation refers to the learning objectives written in the lesson plan; The increase in the value of learning outcomes in the first cycle is 65.63%, the second cycle is 84.38%, the third cycle is 84.38%.